Colorectal cancer detection: time to abandon barium enema?. Issue 2 (19th January 2011) - Shariff, M K; Sheikh, K; Carroll, N R; Whitley, S; Greenberg, D; Parkes, M; Cameron, E A B
Abstract : Objectives: To assess the sensitivity of double contrast barium enema (DCBE) for diagnosing colorectal cancer (CRC). Design: Retrospective evaluation of DCBE performed in the 2 years prior to diagnosis of CRC. Setting: Teaching hospital in Cambridge, UK. Patients: 1310 consecutive cases of CRC identified from cancer registry data. Interventions: DCBE and colonoscopy. Main outcome measures: Sensitivity of DCBE for diagnosing CRC. Results: 215 patients had undergone a DCBE within the 2 years prior to diagnosis with CRC. After excluding those reported as inadequate, 37 of these were reported as normal, giving a sensitivity of 83% (81–85%). Conclusions: The performance of DCBE is inadequate for the exclusion of CRC. Expansion of colonoscopy and CT colonography capacity is urgently required nationally so that DCBE can finally be abandoned as a firstline test in patients at risk of CRC.